Research of the Influence of Air Transportation on Blood Sample Quality - Majić, Zvonimir; Jukić, Irena; Vuk, Tomislav; Pavlin, Stanislav (Promet - Traffic&Transportation, 2012)
In air freight industry, blood samples are classified as time and temperature sensitive biologically produced pharmaceuticals. To determine the level of influence that the handling processes and air transportation have on blood sample quality, a research has been conducted through transportation of whole blood samples on two European scheduled routes. Two shipping models were defined: the standard one without defined transportation temperature regime and the controlled one, where transportation is conducted under appropriate temperature regime. The blood samples were packed and transported respecting all relevant national and international regulations. The analysis was conducted and the results compared to control sample kept in the laboratory. Significant changes were identified on all components analyzed after crosschecking with the control sample.KEY WORDS: regulatory issues, blood sample quality, shipping model, packaging instruction, temperature profiles